Approximation Algorithms for the Maximum Induced Planar and Outerplanar Subgraph Problems - Morgan, Kerri; Farr, Graham (Journal of Graph Algorithms and Applications, 2007)
The task of finding the largest subset of vertices of a graph that induces a planar subgraph is known as the Maximum Induced Planar Subgraph problem (MIPS). In this paper, some new approximation algorithms for MIPS are introduced. The results of an extensive study of the performance of these and existing MIPS approximation algorithms on randomly generated graphs are presented. Efficient algorithms for finding large induced outerplanar graphs are also given. One of these algorithms is shown to find an induced outerplanar subgraph with at least 3n/(d+5/3) vertices for graphs of n vertices with maximum degree at most d. The results presented in this paper indicate that most existing algorithms perform substantially better than the existing lower bounds indicate. <!—->